Case Study of Problem-Solving Ability on Gender Through Collaborative Problem Based Learning - Rahman, Silvani; Sugianto, Sugianto; Ellianawati, Ellianawati (Physics Communication, 2024)
The impact of online learning that has been running for two years has resulted in students becoming less focused and couch potato to study the material provided by the teacher. Provision of stimulation that is still lacking and the lack of laboratory equipment is one of the causes of low problem-solving abilities. This study aims to see the differences and significant improvements in the experimental and control groups based on gender through problem based learning collaborative learning. The research method was quasi-experimental with nonequivalent control group design. Classical calculations of the experimental and control groups have a difference in the significance level (2-tailed) 0.02 0.05 with the N-Gain scores being 0.71 and 0.59. The results of the different test of the experimental group based on gender were (2-tailed) 0.00 0.05 with an N-Gain score of 0.66 and 0.72. The results of the control group's different test showed that the significance level (2-tailed) based on gender was 0.00 0.05. The results of the control group's N-Gain test based on gender were 0.47 and 0.62. The collaborative problem-based learning model encourages the development of critical thinking, problem-solving skills, and communication. Male students have important visuospatial abilities in learning mathematics. Female students have Broca's area which is voluminous and functions to activate language skills.